2013
DOI: 10.1111/srt.12093
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter wave silicon micromachined waveguide probe as an aid for skin diagnosis – results of measurements on phantom material with varied water content

Abstract: The probe has the potential to discriminate between normal and pathological skin tissue. Further, improved information, compared to the optical histological inspection can be obtained, i.e. the complex permittivity characterization is obtained with a high resolution, due to the highly reduced measurement area of the probe tip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…In this first simulation a comparison was made between this model and the more complex three‐layer model comprising: a semi‐infinite layer of air, 1.44 mm layer of skin, and a semi‐infinite layer of fat. The relative complex permittivity of skin was calculated from measurement of reflection coefficients of skin [Dancila et al, ], while the relative complex permittivity of fat tissue was calculated using Gabriel model [Gabriel et al, ]. Comparison between the two models was made for skin with three different water contents, namely 50%, 75%, and 95%, and results presented over the frequency band of 30–100 GHz are in Figure .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In this first simulation a comparison was made between this model and the more complex three‐layer model comprising: a semi‐infinite layer of air, 1.44 mm layer of skin, and a semi‐infinite layer of fat. The relative complex permittivity of skin was calculated from measurement of reflection coefficients of skin [Dancila et al, ], while the relative complex permittivity of fat tissue was calculated using Gabriel model [Gabriel et al, ]. Comparison between the two models was made for skin with three different water contents, namely 50%, 75%, and 95%, and results presented over the frequency band of 30–100 GHz are in Figure .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Using a small monopol antenna, e.g., an extended inner connector of a coaxial probe, to achieve a higher probe resolution than the waveguide cross section has been suggested for measurements on tissue [28], [29], but the distance of the sharp probe tip to the tissue under test has a large influence on the measurement and might be hard to control in in-vivo measurements. Probes that use a small apertures to confine the electromagnetic fields [30], [31] have an energy transfer to the tissue that is inversely proportional to the aperture size, and therefore a compromise between resolution and sensitivity has to be made depending on the intended application area. Probes based on miniaturized open-ended transmission lines, e.g., tapered coaxial probes or tapered planar transmission lines, have been presented for high-resolution measurements on tissue [32]- [35].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a probe is only useful if its characteristics such as resolution, sensing depth, sensitivity, and measurement range are adapted to the targeted application. However, only the minitaturized probes in [29] and [31] were designed for skin cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Gabriel's extrapolated results have been experimentally verified at higher frequencies including 28 GHz [26]. Chahat et al created skin material at 60 GHz [27] and the similar material was shown to work also at lower frequencies [28]. This skin phantom material consists of deionized water, agar, polyethylene-powder and TX-151.…”
Section: B Physical Phantommentioning
confidence: 99%